Effect of barrel temperature and moisture content on the composition and oxidative stability of extruded palm oil in an oil-starch model system. (December 2018) - Wan, Liting; Li, Lin; Jiao, Wenjuan; Mao, Linlu; Li, Bing; Zhang, Xia
Abstract: This study aimed to evaluate changes in the fatty acid composition, oxidative stability and contents of some functional groups of palm oil (PO) during extrusion with corn starch or potato starch under two different extrusion conditions. The contents of saturated fatty acids in extracted PO ranged from 48.5 to 53.06 g/100 g of total fatty acids and were higher than that in unprocessed PO, while the proportions of unsaturated fatty acids were reduced after extrusion. Compared with extrusion at 100 °C with 22 g/100 g moisture content, extrusion at 160 °C with 16 g/100 g moisture content yielded peroxide values, conjugated diene values and p -anisidine values that were greater for extruded PO by ∼1-fold, ∼1-fold and ∼5-fold, respectively, regardless of the type of starch. Moreover, PO extruded with potato starch showed a better oxidative stability than PO extruded with corn starch. Alterations in the O-H, cis C=C, trans C=C and C=O contents in extruded PO were measured by the FTIR-based method. These results showed that extrusion conditions and the type of starch affect the quality of extruded lipids and can be used to choose a formula, determine the extrusion processing parameters and devise the package of oil-containing extruded food products. Highlights: Extrusion significantly reduced the amount of unsaturated fatty acids in palm oil. Different types of starch affected the oxidative stability of extruded palm oil. Effect of extrusion on the contents of some functional groups in palm oil was studied.